2015
DOI: 10.3109/10715762.2015.1067697
|View full text |Cite
|
Sign up to set email alerts
|

The novel NADPH oxidase 4 inhibitor GLX351322 counteracts glucose intolerance in high-fat diet-treated C57BL/6 mice

Abstract: The novel NADPH oxidase 4 inhibitor GLX351322 counteracts glucose intolerance in high-fat diet-treated C57BL/6 mice.. (11) http://dx.doi.org/10. 3109/10715762.2015.1067697 Access to the published version may require subscription. N.B. When citing this work, cite the original published paper. EA and PW performed the experiments. PW, EW and NW designed the experiments, analyzed the results and wrote the manuscript. Free radical research, 49 2 ABSTRACTIn Type 2 diabetes, it has been proposed that pancreatic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 50 publications
1
58
2
1
Order By: Relevance
“…These results suggested that NADPH oxidase-mediated oxidative stress may contribute to glucose intolerance and liver injury during high-fat diet feeding. In addition and in agreement with such hypothesis, a novel NADPH oxidase inhibitor, the GLX351322, was reported to counteract glucose intolerance in high-fat diettreated C57BL/6 mice (Anvari et al, 2015). Another team , catalase and glutathione peroxidase [GPx] (c) parameters were determined.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…These results suggested that NADPH oxidase-mediated oxidative stress may contribute to glucose intolerance and liver injury during high-fat diet feeding. In addition and in agreement with such hypothesis, a novel NADPH oxidase inhibitor, the GLX351322, was reported to counteract glucose intolerance in high-fat diettreated C57BL/6 mice (Anvari et al, 2015). Another team , catalase and glutathione peroxidase [GPx] (c) parameters were determined.…”
Section: Discussionmentioning
confidence: 63%
“…These results suggested that NADPH oxidase‐mediated oxidative stress may contribute to glucose intolerance and liver injury during high‐fat diet feeding. In addition and in agreement with such hypothesis, a novel NADPH oxidase inhibitor, the GLX351322, was reported to counteract glucose intolerance in high‐fat diet‐treated C57BL/6 mice (Anvari et al, ). Another team (Yang et al, ) has reported that oral administration of Salidroside prevented liver injury in the NASH model, through its antioxidant actions to suppress oxidative stress and the free radical‐generating Nox2 in liver.…”
Section: Discussionmentioning
confidence: 66%
“…Our proposition is that the antioxidant drugs used to date are highly unlikely to be able to combat the high levels of b-cell oxidative stress driven continuously by b-cell intrinsic and local environmental factors. One possible approach is to target NADPH oxidases with proof or principle preclinical studies suggesting that the targeting of NOX2 or NOX4 could improve b-cell function , Anvari et al 2015. Our observations that IL22 drives a strong intrinsic antioxidant program in b-cells that decreases production and increases degradation of ROS and RNS open a new pathway to promoting b-cell resilience to oxidative stress caused by lipids, cytokines and protein misfolding.…”
Section: Suppression Of Oxidative Stressmentioning
confidence: 88%
“…A number of compounds, including interfering peptides, have been described as NOX inhibitors and have been recently reviewed in detail (Gatto et al , , Altenhofer et al , ) (Table ). Compounds more recently published include thioridazine, an N‐substituted phenothiazine, with non‐isoform selective NOX activity (Seredenina et al , ); GLX351322, a NOX4‐selective inhibitor (Anvari et al , ); and GSK2795039, a direct NOX2 inhibitor (Hirano et al , ) (Table ). Two of the older compounds that have been widely used as NOX inhibitors are diphenyleneidonium (DPI) and apocynin.…”
Section: Inhibitorsmentioning
confidence: 99%